CD13-Mediated Pegylated Carboxymethyl Chitosan-Capped Mesoporous Silica Nanoparticles for Enhancing the Therapeutic Efficacy of Hepatocellular Carcinoma - Jinhu Liu; Weiwei Mu; Tong Gao; Yuxiao Fang; Na Zhang; Yongjun Liu (MDPI AG, 2023)
Liver cancer, especially hepatocellular carcinoma, is an important cause of cancer-related death, and its incidence is increasing worldwide. Nano drug delivery systems have shown great promise in the treatment of cancers. In order to improve their therapeutic efficacy, it is very important to realize the high accumulation and effective release of drugs at the tumor site. In this manuscript, using doxorubicin (DOX) as a model drug, CD13-targeted mesoporous silica nanoparticles coated with NGR-peptide-modified pegylated carboxymethyl chitosan were constructed (DOX/MSN-CPN). DOX/MSN-CPN comprises a spherical shape with an obvious capping structure and a particle size of 125.01 ± 1.52 nm. With a decrease in pH, DOX/MSN-CPN showed responsive desorption from DOX/MSN-CPN and pH-responsive release of DOX was observed. Meanwhile, DOX/MSN-CPN could be efficiently absorbed through NGR-mediated internalization in vitro and could efficiently deliver DOX to tumor tissues with long accumulation times in vivo, suggesting good active targeting properties. Moreover, significant tumor inhibition has been observed in antitumor studies in vivo. This study provides a strategy of utilizing DOX/MSN-CPN as a nano-platform for drug delivery, which has superb therapeutic efficacy and safety for the treatment of hepatocellular carcinoma both in vivo and in vitro.